INTERPRETATION OF SUB-SURFACE STRUCTURE FROM GEOMAGNETICS DATA SUPPORTED BY GEOGRAPHICS INFORMATION SYSTEM (GIS) AT MURIA VOLCANO COMPLEX, CENTRAL JAVA - Antonius, Tri Santoso (2006)
A geophysical investigation has been done usi ng geomagnetics method at Muria Volcano complex, Central Java. The aims of this resea rc h are to interpret the sub-surface geology structure at Muria Volcano com plex and to apply the Geographies Information System (GIS) as a su pport in geospatial data management, visualization, and analysis. Data acquired usi ng Proton Precession M agnetometer (PPM) and Global Posit i oning System (GPS) Trimble 4600 LS during 21 days, wh ich cover an area of 47,6 km x 45 k m and measureme nt spacing was I - 3 km. Geospatial data consists of geomagnetics, geology, and GPS data. Raw data processing was performed u si ng lG RF (International Geomagnetics Reference Field) and diurnal variation cor rection to obtain total field magnetic anoma l y. Reducti on to horizontal plane was performed at 800 meters height. Upward continuat i on was performed at 12.300 meters hei ght above reference spheroide for regional anomaly and 1800 meters height above reference spheroide for local anomaly. Qualitative i nterpretation was d one by analysing regi onal and local anomaly maps. Quantitative int rpretation was done by 2 Y2 -D modell ing regional and local cross-sect ion anoma l y maps using Mag2DC for Windows software. Geospat ial data management, v isua lization, and anal ysis were done by ArcVie11• 3.2 GIS software. Regional anomaly map showed a dipole anomaly which orien ted south west to north east of Muria Peninsula. Loca l a nomaly map showed two dipole ano maly which oriented north west to south east at no nh and west part of M tu-ia Volcano. It i s i nterpreted that Muria Volcano sub-surface geology structure was controlled by volcanic rock which consist of andesite from Muria Lava, tuff from Muria Tuff, tuffaceous sandstone from Patiayam formation, limestone from Bul u formati on, and cl aystone from g ra yong formation. Muria Peninsula's basement consist of volcanic and volcanocl astic rock at I 0 - 20 km depth below surface.